Machines, computations, and universality: 7th International Conference, MCU 2015 Famagusta, North Cyprus, september 9–11, 2015 proceedings - Durand-Lose, Jérôme Olivier; Nagy, Benedek (Springer Verlag service@springer.de, 2015)
[Abstract Not Available]
7th international conference on Machines, Computations and Universality, MCU 2015 -- 2015-09-09 through 2015-09-11 -- Famagusta -- 140599